Wokół dwóch broszur z czasów chocimskich bojóww 1621 roku (o potrzebie reedycji, relekturyi o niezbędnych rewizjach) = On two brochures from the time of the Chocim Battles in 1621 (on the need for re-edition, re-reading, and necessary revisions) - Sztyber, Radosław (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article presents a critical analysis of two pamphlets related to the 1621 Chocim campaign: the anonymous Rozmowy świeże o nowinach z Ukrainy, z Węgier i z Turek and Chorągiew sauromatcka w Wołoszech by Marcin Paszkowski. The author examines the state of research on early modern Polish ephemeral prints, highlighting numerous bibliographic, editorial, and interpretative errors. The starting point is a call for a rigorous methodology in the study of early printed materials, encompassing precise factual verification, analysis of textual variants, consideration of the historical context, and critical evaluation of previous findings.Regarding Rozmowy, the article corrects inaccuracies concerning the dialogue structure, dating, and historical content, challenging the findings of Juliusz Nowak-Dłużewski and demonstrating the text?s prognostic and propagandistic character. The analysis of Chorągiew identifies unauthorized modernizations in contemporary editions, omissions of key sources (i.a. the diary by Zbigniewski), and the manipulative function of the title, which serves to glorify the noble mass mobilization despite its marginal role in the Chocim campaign. The study concludes with a call for renewed, critical editions and a systematic revision of existing research on early modern occasion literature.
Keywords: kampania chocimska (1621); literatura okolicznościowa; druki ulotne; krytyka edytorska; propaganda; sarmatyzm; Chocim campaign; occasion literature; ephemeral prints; editorial criticism; sarmatism